X (нулевой)=16; ▲х=16.06-16=0.06
f (xнулевой)=√16=4
f'(x нулевой)=1/2*√16=1/8
y=f(xнул.)+f'(xнул)*(▲х)= 4+(1/8)*0.06=4+0.0075=4.0075
Я так понимаю, что у=(1+sin3x)/(cosx+1).
В смысле, что производная от дроби...
Тогда у'=(3cos3x·(1+cosx)-(-sinx)(1+sin3x))/(1+cosx)^2=(3cos3x+3cos3xcosx+sinx+sinxsin3x)/(1+cosx)^2.
Какое? Скинь, что сделать надо вообще
25×3=75кг в 25 ящиках<br />75-15=60кг продали<br />60÷3=20ящиков продали
2.
х×3+15=25×3
3х+15=75
3х=75-15
3х=60
х=60÷3
х=20
3.
(25×3-15)÷3=20
X-48=36
x=36+48
x=84
84-48=36
36=36